Technical Validity of a Customized Assay of Sensitivity to Endocrine Therapy Using Sections from Fixed Breast Cancer Tissue. (2nd July 2020) - Lau, Rosanna; Du, Lili; Chen, Eveline; Fu, Chunxiao; Gould, Rebekah; Marczyk, Michal; Sinn, Bruno V; Layman, Rachel; Bedrosian, Isabelle; Valero, Vicente; Symmans, W Fraser
Abstract: Background: We translated a multigene expression index to predict sensitivity to endocrine therapy for Stage II–III breast cancer (SET2, 3) to hybridization-based expression assays of formalin-fixed paraffin-embedded (FFPE) tissue sections. Here we report the technical validity with FFPE samples, including preanalytical and analytical performance. Methods: We calibrated SET2, 3 from microarrays (Affymetrix U133A) of frozen samples to hybridization-based assays of FFPE tissue, using bead-based QuantiGene Plex (QGP) and slide-based NanoString (NS). The following preanalytical and analytical conditions were tested in controlled studies: replicates within and between frozen and fixed samples, age of paraffin blocks, homogenization of fixed sections versus extracted RNA, core biopsy versus surgically resected tumor, technical replicates, precision over 20 weeks, limiting dilution, linear range, and analytical sensitivity. Lin's concordance correlation coefficient (CCC) was used to measure concordance between measurements. Results: SET2, 3 index was calibrated to use with QGP (CCC 0.94) and NS (CCC 0.93) technical platforms, and was validated in two cohorts of older fixed samples using QGP (CCC 0.72, 0.85) and NS (CCC 0.78, 0.78). QGP assay was concordant using direct homogenization of fixed sections versus purified RNA (CCC 0.97) and between core and surgical sample types (CCC 0.90), with 100% accuracy in technical replicates, 1–9% coefficient of variation over 20 weekly tests, linear range 3.0–11.5 (log2 counts), and analytical sensitivity ≥2.0 (log2 counts). Conclusions: Measurement of the novel SET2, 3 assay was technically valid from fixed tumor sections of biopsy or resection samples using simple, inexpensive, hybridization methods, without the need for RNA purification.